"Everybody Wants a Choice" in Dual Language Education of El Nuevo Sur: Whiteness as the Gloss for Everybody in Media Discourses of Multilingual Education. Issue 6 (2nd November 2021) - Cervantes-Soon, Claudia; Gambrell, James; Kasun, G. Sue; Sun, Wenyang; Freire, Juan A.; Dorner, Lisa M.
ABSTRACT: Georgia and North Carolina are part of what some call the New Latinx South, a region where Latinx populations more than doubled recently. Both states have struggled to educate language minoritized students (evidenced by low graduation rates), yet are among the top three states for numbers of dual language (DL) programs in the Southeast. This model integrates English speakers and speakers of a minoritized language to promote biliteracy for all, disrupting a legacy of English-only education. Such contradictions, along with the Southeast's complex history of racial relations, create tensions and opportunities for DL. Through media content analysis, informed by LatCrit, we examined discourses about DL to determine ways DL is framed and conceived. Findings demonstrate how public discourses perpetuated notions of whom DL should serve, and for what purposes. The discussion identifies spaces of resistance DL supporters can engage to promote democratic, rather than neoliberal, articulations of DL.